Little poems for tiny ears : poems - Oliver, Lin; DePaola, Tomie, 1934-2020 (New York : Nancy Paulsen Books, an imprint of Penguin Group (USA), 2014)
Poems for toddlers and babies describing the discoveries of the wonders of the world around them.
Age: 1-3.
Grade: Pre-school, excluding K.
Keywords: Children's poetry